One Year Prevalence of Venous Thromboembolism in Hospitalized COVID-19 Patients in France: Patients' Characteristics, Time Trends, and Outcomes - Gabet, Amélie; Grave, Clémence; Tuppin, Philippe; Olié, Valérie; Emmerich, Joseph (Thrombosis and Haemostasis, 2022)
Background Patients hospitalized with coronavirus disease-2019 (COVID-19) are at high risk of deep venous thrombosis (DVT) and pulmonary embolism (PE).Objectives The aims were to provide time trends in the 2020 nation-wide prevalence of venous thromboembolism (VTE) in patients hospitalized with a COVID-19 diagnosis in France, and to describe in-hospital and up to 30-day postdischarge death.Methods All patients hospitalized in France with a COVID-19 diagnosis in 2020 were selected. Crude and age-adjusted prevalence of VTE and PE was computed by 4-week intervals and for the overall study period using Poisson regression. Time trends in in-hospital and 30-day postdischarge case-fatality rates were evaluated by comparing each 4-week intervals to weeks 10 to 14 corresponding to the first part of the first lockdown using logistic regression models.Results Among the 287,638 patients hospitalized with a COVID-19 diagnosis in 2020 in France, 14,985 (5.2%) had a concomitant VTE, with 10,453 (3.6%) having PE and 4,532 (1.6%) having DVT. In patients admitted to intensive care units, the crude prevalence of VTE and PE reached 16.1 and 11.0% respectively during the first lockdown. After adjustment, the prevalence of VTE and PE decreased during the year 2020 but a rebound was observed during the second lockdown. In-hospital case-fatality rates among hospitalized COVID-19 patients with PE globally decreased between the first and the second epidemic waves.Conclusion Our study showed a decrease in the incidence of symptomatic VTE and PE in hospitalized COVID-19 patients, and a decreased time trend of outcomes during the second wave compared with the first one.
Keywords: venous thromboembolism; pulmonary embolism; COVID-19; hospitalization; case-fatality